A simple vigor test for adjusting switchgrass seeding rate in marginal and fertile soils. (28th October 2014) - Sadeghpour, Amir; Hashemi, Masoud; Herbert, Stephen J.
Abstract Calculating switchgrass (Panicum virgatum L.) seeding rate is misleading and often causes stand failure. Our objective was to introduce a simple vigor test to adjust the seeding rate and enhance switchgrass establishment and productivity in the establishment year in fertile and marginal soils. Seeding rate for four switchgrass varieties ('Blackwell, ' 'Carthage, ' 'Cave‐in‐Rock' and 'Shawnee') was adjusted ranging from 25 to 125% based on a vigor test. Results indicated increase in seedling emergence and establishment with increasing the seeding rate. Higher established seedlings were recorded from the fertile soil (131 seedlings m−2) compared with the marginal soil (78 seedlings m−2). Based on our previous findings, 100 established seedlings often is considered as a successful establishment; therefore, a 50% (6.89 kg ha−1) and 100% (13.82 kg ha−1) adjusted seeding rates could provide sufficient stand density (111 and 94 seedlings m−2) in the establishment year in fertile and marginal soils, respectively.